Clinical and Functional Characteristics of COPD Patients Across GOLD Classifications: Results of a Multicenter Observational Study. (4th July 2019) - Radovanovic, Dejan; Contoli, Marco; Marco, Fabiano Di; Sotgiu, Giovanni; Pelaia, Girolamo; Braido, Fulvio; Corsico, Angelo Guido; Micheletto, Claudio; Rogliani, Paola; Scichilone, Nicola; Saderi, Laura; Santus, Pierachille; et al.
Abstract: Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease. The severity grading systems proposed by the Global initiative for Chronic Obstructive Lung Disease (GOLD) have changed over time. The aim of the study was to evaluate if the different GOLD classifications can capture the complexity of the disease by investigating the distribution of lung function and clinical parameters across the GOLD classification systems. This was an observational, retrospective, multicentre study. COPD patients were stratified according to the GOLD severity grading proposed in the 2007, and to the ABCD assessment tool present in the 2011, and 2017 versions of the initiative. Data from body plethysmography, DLCO, comorbidities, exacerbation history, pharmacological therapy and eosinophil counts were collected. A total of 1360 patients (73.4% males) were included in the analysis. Overall, 37% of the patients were severe-very severe according to GOLD 2007. Compared with GOLD 2011, applying the GOLD 2017 criteria, the proportion of the at risk categories (C and D) was reduced by ∼23%. Impairment in inspiratory capacity, DLCO and the prevalence of emphysema paralleled the GOLD 2007 classification only. The proportion of patients with ≥ 200 eosinophils/µL was higher in GOLD 2007 stages 3–4 compared with stages 1–2 ( P = 0.008). Eosinophil levels were similar across risk classes in GOLD 2011 and 2017. Overall, 41.8% and 52.4% of the patients in the low risk groups according to GOLD 2011 and 2017 were exposed to inhaled corticosteroids. The GOLD 2011 and 2017 classifications, despite exploring symptoms and exacerbations, might miss other relevant patients' clinical characteristics such as lung function and phenotypes, which have a significant impact on outcomes and disease severity.